Penerapan Word Square untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 38 Parepare - Kamaruddin Hasan; Shasliani Shasliani; Nur Annisa Putri S (STKIP Andi Matappa Pangkep, 2023)
This study aims to improve the process and student learning outcomes by applying the Word Square type of cooperative learning model. his research is a Classroom Action Research (CAR) with a qualitative approach. Data collection techniques used are observation, tests and documentation. The subjects of this study were the teacher (researcher) and the fifth grade students, totaling 16 people. Based on the research data in the first cycle, the teacher's observations were in the good category (B), the student's observations were in the sufficient category (C) and the student learning outcomes showed an average value of 72. In the second cycle the teacher's observations were in the good category (B), the results of student observations were in the good category (B) and the student learning outcomes showed an average value of 85. This shows that the learning outcomes of fifth grade students of UPTD SD Negeri 38 Parepare after being implemented Word Square cooperative learning model experienced a significant increase.